Developing Nahma (Nahwu Matching) for Basic Nahwu Learning Game: A Need Assessment Study - Mohamad Yusuf Ahmad Hasyim; Bernandus Wahyudi Joko Susilo; Jamat Jamil (Jurnal Alsinatuna, 2022)
In this epidemic era, teachers are expected to build a successful learning environment in conjunction with online learning. Basic nahwu learning is one of the lessons affected by the pandemic situation. Learning the Arabic language system is increasingly difficult to do online because the Arabic language system is very different from Indonesian, as the learners' mother language. The presentation of linguistic rules clearly cannot be done directly. Educators are responsible for innovating nahwu learning through the unity-based Nahma educational game "Nahwu Matching" so that learners can easily understand and avoid boredom during the full online learning. The use of educational games is the right solution to overcome this problem. The aims of this study are: (1) to find out the needs of lecturers and students, (2) to describe the prototype picture of the Nahma. The data of this study were obtained through test and non-test data. The tool of the test is a written test while tools of the non-test data are interviews, observations, and questionnaires on the needs of lecturers and students. Based on the findings, it can be stated that both students and teachers require engaging learning applications for Nahwu that can successfully assist the learning process.